How to Improve Scientific Publication Performance of Private University Lecturers: an Empirical Analysis on Individual and Institutional Factors - Harsasi, Mairani; Hutagaol, Manuntun Parulian; Baga, Lukman M; Sailah, Illah (Jurnal Organisasi dan Manajemen, 2021)
Indonesian scientific publications on Scopus show encouraging increase by being listed as number 1 in Southeast Asia. However, fewer literary contribution by private university compared to those made by state university. Thus this study investigates which factors will impact publication performance of private university lecturers. Using multiple linear regression analysis of 226 data, it is found that motivation, self-efficacy, research skills, research time, and training are proven to have positive impact on publication performance. Findings. Teaching workload was found to have significant negative impact, while supporting resources were the only variable that had no impact on publication performance. This research has contribution towards institutional policies in encouraging lecturers to produce scientific publications by strengthening the influencing factors.